MANAGING ENGLISH COMPETENCE AS A COMPETITIVE ADVANTAGE: CASE STUDY AT STES ISLAMIC VILLAGE TANGERANG - Muizzudin Muizzudin (STES Islamic Village, 2019)
The purpose of this research is to know the level of English competence the students of the seventh semester at STES Islamic Village Tangerang in the academic year of 2018-2019. The instrument of this research is TOEFL paper-based test called TOEFL Prediction. The result of this research showed out of forty students only one student (2.5 %) achieved the minimum score required by the institution. Most of them (97.5 %) could not reach the minimum score. Although this is still the initial step to manage English competence as a competitive advantage for STES Islamic Village Tangerang. The research result will lead to the necessity of follow-up research to do so..